2006
DOI: 10.1002/ejic.200501006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of β‐Cyclodextrin and Permethylated β‐Cyclodextrin Inclusion Compounds of Cyclopentadienyl Metal Carbonyl Complexes

Abstract: [CpM(CO) n Cl] complexes with M = Fe (n = 2) and Mo (n = 3) have been immobilised in plain β-cyclodextrin (β-CD) and permethylated β-CD (TRIMEB) by methods tailored according to the stabilities and solubilities of the individual components. Four adducts were obtained with a 1:1 host/guest stoichiometry. The compounds were studied by powder X-ray diffraction (XRD), thermogravimetric analysis (TGA), 13 C{ 1 H} CP/MAS NMR and FTIR spectroscopy. A comparison of the experimental powder XRD data for the TRIMEB/[CpMo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…In these compounds, b-CD molecules are arranged in a cage packing mode, not much different from that found for pure b-CD, thus indicating that inclusion of the guest 2 has not significantly altered the structure of this host. This kind of packing, although seemingly surprising for bulky guests, was already observed for the compound b-CDÁ[CpMo(CO) 3 Cl] in a previous work (Braga et al 2006a).…”
Section: X-ray Diffraction Studiesmentioning
confidence: 60%
See 3 more Smart Citations
“…In these compounds, b-CD molecules are arranged in a cage packing mode, not much different from that found for pure b-CD, thus indicating that inclusion of the guest 2 has not significantly altered the structure of this host. This kind of packing, although seemingly surprising for bulky guests, was already observed for the compound b-CDÁ[CpMo(CO) 3 Cl] in a previous work (Braga et al 2006a).…”
Section: X-ray Diffraction Studiesmentioning
confidence: 60%
“…Nevertheless, we found that it works particularly well for the methylated cyclodextrin, TRIMEB, due to its high solubility in these media. In fact, the same method has been previously successfully employed by some of us (Braga et al 2006a;Pereira et al 2007). The adduct b-CDÁ[Ru( [9]aneS 3 )phenCl]Cl (4) was prepared by co-dissolution in water/ethanol (50/50) followed by freeze-drying to obtain an orange microcrystalline solid.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…[10] Moreover, CDs are known to bind organometallic complexes containing aromatic constituents and such encapsulated complexes often exhibit markedly different physical and chemical properties. [11] Nevertheless, only very few examples of such inclusion complexes reported in the literature have been successfully characterized by single-crystal X-ray diffraction. [12] We have recently reported the application of the N-salicylidene hydrazide ligand system for generating vanadium(V) complexes with a variety of functional groups attached to the ligand core.…”
Section: Introductionmentioning
confidence: 99%